Epidemiology of malaria in two Eastern districts of Nepal - Parajuli, K; Ghimire, P (Kathmandu University Medical Journal, 2010)
Backgrounds: Malaria is one of the major public health problems in Southeast Asia including Nepal having relatively high burden of malaria. Jhapa and Morang districts are malaria endemic plain area of South-eastern part of Nepal Objectives: The evaluate the recent epidemiology of malaria situation in Jhapa and Morang districts, which are the districts in eastern Nepal with high transmission of malaria and to assess the knowledge, attitudes and practices of the people in prevention and treatment for malaria infection. Materials and methods: This descriptive cross-sectional study was carried out with volunteer participation of suspected malaria patients seeking care at the government of Nepal managed primary health care centres located in 2 malaria endemic districts in eastern Nepal. Conventional Giemsa stained thick and thin blood smears prepared from finger prick blood were examined following standard protocols. Suspected patients' / attendants' knowledge on malaria, disease symptoms, prevention and control measures were assessed using a structured questionnaire. Chi square and Fisher exact test were used for statistical analysis of the data. Results: Among the total 199 malaria suspected cases studied, 32 (16.1%) cases were confirmed by microscopic findings; where, P. vivax was 12.6% (25/199) and P. falciparum in only 3.1% (6/199). The highest numbers of cases were in age group 20-29 years. Among the total positive cases 75% were male and 37.5% were labourers in occupation. Among the total cases, 32 had provided the history of recent travel to malaria endemic area in India, among them 43.8% (P<0.001) were found to be infected with the malarial parasites (P<0.001). Among the total cases, 69.7% showed some knowledge of malaria, among which fever was the most common symptom mentioned by 68.3%. Occupation (P<0.001) and education (P<0.001) were found significantly associated with the knowledge on mode of transmission. Conclusion: Jhapa district showed higher SPR than Morang, which indicated that Jhapa may be more malaria affected than Morang. Knowledge on malaria transmission and preventive measures are still lacking in deep villages, in spite of different efforts of the government. To improve the malaria morbidity in the districts, health education of the most marginalized people through audio visual methods may be beneficial. Key words: Epidemiology; Malaria; Knowledge; Practice; Eastern Nepal DOI: 10.3126/kumj.v8i1.3221 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 45-50